Entangled Knowledge Scientific Discourses and Cultural Difference (Volume 4) - Hock, Klaus; Mackenthun, Gesa (2012)
The intimate relationship between global European expansion since the early modern period and the concurrent beginnings of the scientific revolution has long been acknowledged. The contributions in this volume approach the entanglement of science and cultural encounters - many of them in colonial settings - from a variety of perspectives. Historical and historiographical survey essays sketch a transcultural history of knowledge and conduct a critical dialogue between the recent academic fields of Postcolonial Studies and Science & Empire Studies; a series of case studies explores the topos of Europe's 'great inventions', the scientific exploitation of culturally unfamiliar people and objects, the representation of indigenous cultures in discourses of geographical exploration, as well as non-European scientific practices. 'Entangled Knowledges' also refers to the critical practices of scholarship: various essays investigate scholarship's own failures in self-reflexivity, arising from an uncritical appropriation of cultural stereotypes and colonial myths, of which the discourse of Orientalism in historiography and residual racialist assumptions in modern genetics serve as examples. The volume thus contributes to the study of cultural and colonial relations as well as to the history of science and scholarship.